DEVELOPMENT OF A COMMUNITY HEALTH MONITORING INFORMATION SYSTEM IN PALELEH DISTRICT - Bumbuluto, Angki; Syafri Tuloli, Mohamad; Dwinanto, Arif (Diffusion: Journal of Systems and Information Technology, 2025)
It is hoped that this system can overcome various problems in recording and registering public health, as well as making it easier to carry out health checks and access health history. Health monitoring is a very important thing to do so that the government can determine what actions or medical assistance will be prioritized, therefore a "Development of a Public Health Monitoring Information System in Paleleh District" is needed with the aim of designing an information system that can assist Public Health. Effectively, the research method used is the Development Live Cycle (SDLC) System which includes the Planning, Analysis, Design, Implementation and Testing Stages. The result of this research is the development of an application that allows real-time public health checks. This system has passed a series of Black box tests. The conclusion of this research is that the information system has been developed and can help the head of the Paleleh community health center.